Time and the Problems of Television: Three Images - Timothy Barker (Philosophies, 2019)
In this paper I look at three images and use them to discuss television and the conditions for the representation of time in the twenty-first century. The first image is from the UK’s Channel 4 news report following the November 2015 terror attacks in Paris. The paper begins by offering a theoretical critique of this televisual image and explores the grounding offered for the representation of fear and the contingent. From here, I explore two images from the experimental beginnings of television, which can be seen to provide the historical and technical conditions for the first image. The paper is media philosophical in method, critically analysing the way television can represent time and events by looking to its technical operation and its history as a technology rooted in solutions to time-based problems.